(untitled) (Journal of Business and Technology (Dhaka), 2015)
The main focus of this study is the impact of shrimp culture on livelihood activities of female labor through income and occupation, food consumption, hazardous working environment and so on. Female labors involved in different activities of various shrimp sectors are characterized by diseases, poor income and nutritional status, low quality working environment, harassment and unsocial activities of mischievous persons, social negligence and poor living standard. Moreover, different shrimp-related activities adversely affect the health status of female labor through diseases. The hypothesis of this study is job categories in shrimp sectors deteriorate the health status of female labor in south-western regions of Bangladesh. It tested through Pearsons chi-square test with cross table analysis. The major objectives of this study are: to know the health status of female labors and occurrence of diseases that result from their occupation; to know the income level as it is associated with food consumption through which health status is maintained. In this study a more or less randomly collected respondents of 120 have been utilized for structured questionnaire survey. Beside, FGD (Focus Group Discussion) method has been used for in depth information. Based on the field data it can be seen that various diseases spread out among female labors through different modes of work, overtime work and unhealthy working environment. These disease occurrences also depend on nutritional status that is determined by income and food consumption of the respondents. Ultimately, poor economic condition leads toward vulnerable health situation. Generally, the female workers suffer from inadequacy of money at the time of treatment. In other sense, female labors face severe income discrimination and irregularity of payment in the work place because they cannot raise their voice. With meager wage they meet their consumption-needs and many of them cannot afford money in time of diseases. For this reason they do not seek treatment. DOI: http://dx.doi.org/10.3329/jbt.v9i1.22774 Journal of Business and Technology (Dhaka) Vol.9(1) 2014; 1-22